Efficacy of Vaccination with Different Combinations of MF59-Adjuvanted and Nonadjuvanted Seasonal and Pandemic Influenza Vaccines against Pandemic H1N1 (2009) Influenza Virus Infection in Ferrets - van den Brand, Judith M. A. (American Society for Microbiology (ASM), 2011)
Serum antibodies induced by seasonal influenza or seasonal influenza vaccination exhibit limited or no cross-reactivity against the 2009 pandemic swine-origin influenza virus of the H1N1 subtype (pH1N1). Ferrets immunized once or twice with MF59-adjuvanted seasonal influenza vaccine exhibited significantly reduced lung virus titers but no substantial clinical protection against pH1N1-associated disease. However, priming with MF59-adjuvanted seasonal influenza vaccine significantly increased the efficacy of a pandemic MF59-adjuvanted influenza vaccine against pH1N1 challenge. Elucidating the mechanism involved in this priming principle will contribute to our understanding of vaccine- and infection-induced correlates of protection. Furthermore, a practical consequence of these findings is that during an emerging pandemic, the implementation of a priming strategy with an available adjuvanted seasonal vaccine to precede the eventual pandemic vaccination campaign may be useful and life-saving.